20 POINTS BRAINLIEST math
![20 POINTS BRAINLIEST math class=](https://us-static.z-dn.net/files/d58/a2451d3690d258c4a05760e7da062f21.png)
Answer:
OPTION C
Step-by-step explanation:
Given: [tex]$ y = \sqrt{36 - 72} + 5 $[/tex]
This can be rewritten as: [tex]$ y = \sqrt{36(x - 2)} + 5 $[/tex]
Also, since [tex]$ \sqrt{ab} = \sqrt{a}.\sqrt{b} $[/tex]
[tex]$ \implies y = \sqrt{36}.\sqrt{x - 2} + 5 $[/tex]
We know that [tex]$ \sqrt{36} = 6 $[/tex]
[tex]$ \implies y = 6\sqrt{x - 2} + 5 $[/tex]
Hence, Option C would the answer.